Positive steady states of the Holling-Tanner prey-predator model with diffusion - Peng, Rui; Wang, Mingxin (Proceedings of the Royal Society of Edinburgh. Section A. Mathematics, 2005)
This paper is concerned with the Holling-Tanner prey-predator model with diffusion subject to the homogeneous Neumann boundary condition. We obtain the existence and non-existence of positive non-constant steady states.